The Role of Vitamin D in the Pathomechanism of Inflammatory Bowel Disease (IBD) and its Therapeutic Implications - a literature review - Tomaszewska, Wiktoria Maria; Siudziński, Paweł; Łyko, Mateusz; Skoczylas, Alicja; Kurasz, Jakub; Maj, Wojciech; Podlasiewicz, Wiktoria; Pala, Katarzyna; Dudziak, Piotr; Nowak, Anna; et al. (Journal of Education, Health and Sport, 2025)
Introduction: Vitamin D holds a crucial role in the pathogenesis of inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC). Its mechanisms of action involve immune system modulation, specifically by reducing the production of pro-inflammatory cytokines, such as IL-6 and TNF-α, while enhancing the levels of anti-inflammatory cytokines, such as IL-10. Furthermore, vitamin D contributes to the maintenance of intestinal barrier integrity by strengthening epithelial tight junctions. It also exerts a beneficial influence on the intestinal microbiota, promoting the proliferation of beneficial bacterial species, such as Faecalibacterium prausnitzii, which play a role in mitigating disease relapses and sustaining immune homeostasis. Although vitamin D supplementation demonstrates potential in reducing inflammation and improving clinical outcomes, the observed effects remain varied and require further investigation. Aim: The purpose of this study was to analyze the mechanisms of action of vitamin D in the context of the pathogenesis of inflammatory bowel disease (IBD) and its potential therapeutic applications, with particular emphasis on clinical studies evaluating vitamin D supplementation.